In Situ Analysis of Solid Electrolyte Interface over Si Based Anodes Using Diffuse Reflectance Infrared Fourier Transform Spectroscopy. (21st April 2017) - Yohannes, Yonas Beyene; Wu, Nae-Lih; Lin, Shawn D.
Abstract : In this work the formation and evolution of solid electrolyte interphase (SEI) layer on a Silicon based electrode in electrolytes containing 1 M LiPF6 /EC:EMC (1:2):VC (2 % wt) and 1 M LiPF6 /EC:EMC (1:2):VC (2 % wt) + FEC (10 % wt) was investigated by in-situ DRIFT spectroscopy. Electrolyte without FEC is composed primarily of poly (VC), polycarbonates and lithium carbonate. Incorporation of 10 % wt FEC results with the formation of poly (VC/FEC), polycarbonates, lithium carbonate species, alkoxy species and alkyl phosphates. Incorporation of FEC also result with the increase in the formation of poly (VC/FEC). Moreover in the course of 2nd discharging, incorporation of FEC impedes the decomposition of both solvent and salt anion reduction.